Estimation of uncertainty of laser interferometer measurement in industrial robot accuracy tests - Józwik, Jerzy; Jacniacka, Elżbieta; Ostrowski, Dawid (ITM web of conferences, 2017)
The subject of this article is the assessment of measurement uncertainty of the Renishaw XL80 laser interferometer in MOTOMAN HP20 industrial robot inaccuracy test. The paper presents the methodology for estimating the measurement uncertainty of the system used in tests. Estimates of standard and extended uncertainty were calculated for the given research method. These uncertainties are based on the information included in the device calibration certificate (method B) but also on the basis of measurements and statistics (method A). The authors proposed their own research methodology, taking into account measurement capabilities of the applied system and the specific character of the robot work. Calculations employed universal computing systems based on standard algorithms. The results obtained from the research and calculations precisely defined key uncertainties allowing for objective evaluation of industrial robot errors identified by the Renishaw XL80 system.